The Prevalence of Vaginal Microorganisms in Pregnant Women with Preterm Labor and Preterm Birth - Choi, Seong Jin (The Korean Society for Laboratory Medicine, 2012)
BACKGROUND: To investigate the risk factors for vaginal infections and antimicrobial susceptibilities of vaginal microorganisms among women who experienced preterm birth (PTB), we compared the prevalence of vaginal microorganisms between women who experienced preterm labor (PTL) without preterm delivery and spontaneous PTB. METHODS: Vaginal swab specimens from 126 pregnant women who experienced PTL were tested for group B streptococcus (GBS), Mycoplasma hominis, Mycoplasma genitalium, Ureaplasma urealyticum, Chlamydia trachomatis, Trichomonas vaginalis, Neisseria gonorrhoeae, Treponema pallidum, herpes simplex virus (HSV) I and II, and bacterial vaginosis. A control group of 91 pregnant women was tested for GBS. Antimicrobial susceptibility tests were performed for GBS, M. hominis, and U. urealyticum. RESULTS: The overall detection rates for each microorganism were: U. urealyticum, 62.7%; M. hominis, 12.7%; GBS, 7.9%; C. trachomatis, 2.4%; and HSV type II, 0.8%. The colonization rate of GBS in control group was 17.6%. The prevalence of GBS, M. hominis, and U. urealyticum in PTL without preterm delivery and spontaneous PTB were 3.8% and 8.7% (relative risk [RR], 2.26), 3.8% and 17.3% (RR, 4.52), and 53.8% and 60.9% (RR, 1.13), respectively, showing no significant difference between the 2 groups. The detection rate of M. hominis by PCR was higher than that by culture method (11.1% vs. 4.0%, P=0.010). The detection rates of U. urealyticum by PCR and culture method were 16.7% and 57.1%, respectively. CONCLUSIONS: There was no significant difference in the prevalence of GBS, M. hominis, and U. urealyticum between the spontaneous PTB and PTL without preterm delivery groups.